Comportamiento agronomico y calidad del grano de siete cultivares de cafe manejado bajo sombra, Masatepe, Nicaragua - Suarez Rivera, A. del C.=700 1 Picado Aragon, J.R.; Munguia Hernandez, R.; Haggar, J.
(Es, En)
Ilus., 20 ref.
Keywords: COFFEA ARABICA; VARIEDADES; EVALUACION; CARACTERISTICAS AGRONOMICAS; CALIDAD; SEMILLA; PROPIEDADES ORGANOLEPTICAS; FITOMEJORAMIENTO; INVESTIGACION DE MERCADOS; NICARAGUA; MASATEPE; LA CALERA